GAMBAR SAMPUL CHARLIE HEBDO SEBAGAI KRITIK TERHADAP FANATISME BERAGAMA - Miranda, Airin (Universitas Hasanuddin, 2019)
Charlie Hebdo is a satirical and leftist weekly newspaper in France. This weekly is known for its idealism as opposed to all forms of fanaticism. Since the attack that took place on January 7, 2015, Charlie Hebdo has become a topic of conversation for many. The attack that caused the deaths of 12 famous French caricaturists was easily attributed to Islamophobia and the idea of terrorism. This study analyzes some of Charlie Hebdo covers on the theme of Islam to show its point of view on the ideology and practice of the Islamic religion. Data collection is done online. With the critical discourse analysis, the signs found in Charlie Hebdo's cover image will be related to the context of the event surrounding its publication. The results will show whether the Islamic-themed caricature of some of Charlie Hebdo is a form of Islamophobia or a critique against fanaticism. The results of this study would provide a better understanding of French society, particularly its view of religious life in France.